Agronomic Performance for Tuber Characters in Winged Bean [Psophocarpus tetragonolobus (L.) DC.] - Kant, Achal; Nandan, R.; Kole, P. C. (International Journal of Economic Plants, 2018)
The present investigation was carried out to identify the tuber producing genotypes from a pool of 27 genotypes of winged bean. The experiments were conducted at Vegetable Research Farm of Banaras Hindu University, Varanasi, Uttar Pradesh during kharif season of 2014 and 2015. Among 27 genotypes, 22 genotypes were tuberous roots producing, while rest five genotypes were non-tuberous. These tubers forming 22 genotypes were further grown for evaluation of their performance in next kharif season of 2015. Based on different agronomic characters, the accessions RWB-15 recorded the highest values for tuber yield plant-1 (g), tuber length (cm), tuber dry matter (%) and total sugar content (g g-1) in tuber with moderate values for tuber breadth (cm), 100 seeds weight (g) and tuber crude protein (%), followed by Ambika-13-4, RMDWB-1, Ambika WB -11-2 and IC-178292 which appeared promising for different tuber characters. Therefore, RWB-15 along with the above four accessions could be tested under different agronomic practices for commercial production and human consumption of this tuber producing legume.